Reproductive biology and fruit setting of Passiflora quadrangularis L. (Giant Granadilla) in East Malaysia - Shahbani, Nur Shahirah; Ramaiya, Shiamala Devi; Saupi, Noorasmah; Bujang, Japar Sidik; Zakaria @ Ya, Muta Harah (Universiti Putra Malaysia Press, 2020)
Passiflora quadrangularis L., also known as giant granadilla, belongs to the family Passifloraceae together with the well-known species Passiflora edulis Sims. This species has received attention from growers in recent years due to its aromatic flowers, unique and excellent fruit flavor and phytotherapeutic properties. Despite the numerous health benefits of this Passiflora species, information on their agronomical features and production is scarce. Therefore, the objective of this study was to examine the reproductive biology and fruit setting of P. quadrangularis cultivated in Sarawak, Malaysia. The findings revealed that the giant granadilla was a steady-state species that produced flowers lasting for only one day. Passiflora quadrangularis started to produce flowers 3 months after transplantation, followed by fruiting two months after anthesis. In East Malaysia, the flowers started blooming at dawn (0625±0.17 hours) followed by anthesis at 0806±0.23 hours and remained open until sunset. In contrast to P. edulis which flowered all year round, this species only exhibited two peaks, with a minor peak recorded from January-March and a major peak from September-December, coinciding with warm temperatures and moderate rainy season. Good fruit yields were recorded which was attributed to the ability for self-pollination due to autogamy and geitonogamy, in addition to the presence of effective pollinators. The yearly production of P. quadrangularis, produced relatively larger fruit with weights ranging from 884.4-2892.7 g, was 20,151.36 kg ha-1 (8993 fruits). Detailed information on the reproductive behavior of P. quadrangularis growing in local climates can be used for commercial cultivation and future breeding studies.